Chromatography and spectroscopy methods for the analysis of nicotine and other chemical ingredients in e-liquid formulation: a review - Abdull Manap, Mohd Rashidi; Hamzah, Noor Hazfalinda; Aina Kholili, Qhurratul; Abu Hasan, Fatin; Alhumaira, Azhana (Universiti Putra Malaysia Press, 2024)
Spectroscopy and chromatography methods have become the most preferred techniques for detecting ingredients in e-liquid analysis. Both methods are widely used for separating and quantifying volatile compounds in a sample, providing individual chemical information in complex mixtures. This paper aims to review the detection and quantification of nicotine and other chemical ingredients in e-liquid used in e-cigarettes. E-cigarettes use the evaporation-condensation principle of aerosolization to produce an inhaled vapor containing nicotine, excipients, and flavoring agents. This review covers sample preparation, identification, and quantification of nicotine and other ingredients using chromatography and spectroscopy analysis. The spectroscopy methods are useful for quickly identifying and quantifying volatile compounds, including propylene glycol (PG), vegetable glycol (VG), and nicotine, while spectroscopic methods, particularly the Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) method, have lower analytical performance compared to chromatography methods in detecting nicotine and other chemical ingredients. Based on the review, chromatographic methods are the primary option for analyzing nicotine in all e-liquid samples, offering a better alternative for a future study with the presence of multiple detectors.